Implementation of Go Public in the Development Indonesian Company Law (Case of PT. Astra International) - Laniati, Ratna; Rahayu, Sang Ayu Putu; Daren, Bastian Chris (Law Research Review Quarterly, 2023)
In the competitive business landscape of Indonesia, companies vie for prominence within their respective sectors. The capital market emerges as a pivotal avenue for enterprises to secure financial resources crucial for sustaining and expanding their operations. "Going public" through a public offering, wherein a company sells shares to investors, is a strategic approach adopted by numerous firms, including PT. Astra International Tbk. This process is perceived not only as a means to enhance corporate image but also to procure capital for purposes such as expansion, product development, and strategic business amalgamations. The primary objectives of this study are twofold: First, to elucidate the procedural intricacies a company in Indonesia undergoes to attain the status of a publicly traded entity, and second, to scrutinize the practical facets of the "Go Public" process, focusing on its implementation at PT. Astra International. The outcomes of this study reveal that going public involves the regulated offering of shares or securities to the public, as stipulated by Law no. 8 of 1995 concerning Capital Markets and its associated regulatory frameworks. In addition, PT. Astra International Tbk., having undergone this transformation and been listed on the Jakarta Stock Exchange since April 4, 1990, aspires to fortify its financial structure, enhance operational performance, and realize predetermined expansion objectives through the going public process. While this transition affords companies access to expanded funding sources, it concurrently imposes new responsibilities and repercussions that necessitate careful consideration and management by the concerned entity.